2011
DOI: 10.4028/www.scientific.net/amr.189-193.3920
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cooling Condition on Zr-Rich Core Formation and Grain Size in Mg Alloy

Abstract: The effects of cooling condition on the Zr-rich core formation and grain size in Mg-Zr alloys were investigated in this study. Four moulds with various cooling rates and different Zr additions were used. The results show that when Zr addition was 1.2%, the Zr-rich cores were round and their diameters increased with decreased cooling rates. When Zr addition content was decreased to 0.7%, Zr-rich cores formed only in the sand mould with the lowest cooling rate used in this study, and the morphology changed to ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Various zirconium was added to the melt in the form of Mg-Zr master alloy preheated at 250˚C. The morphology and distribution of Zr particles in Mg-Zr master used was given in detail in Ref [8]. RJ 2 cover flux(main compositons:38-46% MgCl 2 ,32-40%KCl, 5-8%BaCl, 3-5%BaCl, 3-5%CaF 2 , and 8% NaCl+CaCl) was used as a mixed protection and RJ5 flux(main compositons:24-30% MgCl 2 , 20-26%KCl, 28-31%BaCl 2 , 13-15%CaF 2 , and 8% NaCl+CaCl) was used as refining agent.…”
Section: Methodsmentioning
confidence: 99%
“…Various zirconium was added to the melt in the form of Mg-Zr master alloy preheated at 250˚C. The morphology and distribution of Zr particles in Mg-Zr master used was given in detail in Ref [8]. RJ 2 cover flux(main compositons:38-46% MgCl 2 ,32-40%KCl, 5-8%BaCl, 3-5%BaCl, 3-5%CaF 2 , and 8% NaCl+CaCl) was used as a mixed protection and RJ5 flux(main compositons:24-30% MgCl 2 , 20-26%KCl, 28-31%BaCl 2 , 13-15%CaF 2 , and 8% NaCl+CaCl) was used as refining agent.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, increasing the cooling rate (Ṫ) results in a decrease in grain size. For example, Liu et al [62] showed that the grain size of Mg-Zr binary alloys (0.3, 0.7 or 1.2Zr) decreased with increasing cooling rate from sand mold to Cu mold. Sun et al [63] found that the relationship between the grain size of Mg-Y-Zr alloy (1~9Y, 0.1~0.5Zr) and 1 𝑄𝑇 ⁄ could be linearly fitted at a cooling rate ≤80 °C/s (Figure 9 shows Mg-1Y-Zr alloy as an example of this phenomenon).…”
Section: Effect Of Cooling Conditionmentioning
confidence: 99%